MEDIA TELEVISI SEBAGAI SARANA PENDIDIKAN DEMOKRASI ? : Wacana Menuntut Kelengkapan Peran Media dalam Demokrasi (Program Studi Ilmu Komunikasi Universitas Muhammadiyah Yogyakarta, 2017)
This article explains about the presence of commercials televison in indonesia had many dynamic, expecially for politic phenomenon. When news has been much consider to one candidate, its mean media become a partisan of politic organization. This is so due to fact that mass media now depend mostly on controlled by the owner media who have interest in making good images in public eyes to through political choice. Keywords : televison, Journalist, Â political media and democratization